2020
DOI: 10.4149/bll_2020_038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the anatomical location and the number of metastatic lymph nodes on gastric cancer patient´s survival

Abstract: BACKGROUND: The most serious problem in surgical treatment of gastric cancer includes the area of resection and the extent of lymphadenectomy. The extent of gastric resection is determined by the extent of tumor affection. The aim of radical surgical intervention is to achieve microscopically clear resection line, since R0 resection is the main criterion for the patient´s prognosis. Curative surgical resection for gastric cancer includes the lymph nodes dissection. In the treatment of gastric cancer, there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This procedure is currently considered the gold standard in the treatment of gastric cancer (7). The study results of Duchon et al showed that in between patient´s prognosis and the anatomic localization of the affected lymph nodes in case of gastric cancer patient´s survival was the strongest correlation, however this correlation was not statistically signifi cant (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure is currently considered the gold standard in the treatment of gastric cancer (7). The study results of Duchon et al showed that in between patient´s prognosis and the anatomic localization of the affected lymph nodes in case of gastric cancer patient´s survival was the strongest correlation, however this correlation was not statistically signifi cant (30).…”
Section: Discussionmentioning
confidence: 99%
“…on the extent of the tumour. In radical surgery, the goal is to achieve a clear resection edge (5). Radical gastrectomy for gastric cancer is the basic treatment in the patients with advanced disease (6).…”
Section: U N C O R R E C T E Dmentioning
confidence: 99%
See 1 more Smart Citation